Inclusive education is a right, right? - Thomas, Matthew Krehl Edward; Heng, Leechin; Walker, Peter (Studies in inclusive education (Sense Publishers), 2021)
"Overarching principles of human rights which shore up a nearly 30-year history of international efforts to develop educational systems that are responsive to the needs of all. Arguably the most widely recognised international inclusive education policy, the Salamanca Statement released in 1994 from the United Nations Education, Science and Cultural Organisation (UNESCO), recognised that every child has a basic right to education. In so doing, however, it drew a line around special needs as a particular emphasis, in globalising efforts towards equal opportunity through decrees for first principles of universally attainable privileges. Considered a watershed moment in global responses to educational exclusion, the Salamanca Statement was core to increasing awareness among nations of the need for fostering more inclusive education policy and practice. Nonetheless, the liberal ideologies that frame human rights in inclusive education are seldom called into question, despite perpetual marginalisation and disadvantage post Salamanca. Inclusive Education Is a Right, Right? brings the many together to consider educational democracy at a moment in global history where the political order fractures populations, and the displacement of socio-economic participation is displayed in every news bulletin - true, fake or otherwise. Under these conditions, the significance of academic activism, wherein diverse perspectives, methodologies and theoretical approaches are put to work to increase equity in education, has perhaps never been so stark. Across the collection the combined chapters engage with researchers, students, education professionals and leaders, advocacy organisations, and people experiencing exclusion and consider human rights in relation to inclusive education. Contributors are: Kate Anderson, Alison Baker, Tim Corcoran, Edwin Creely, Jenny Duke, Peng-Sim Eng, Leechin Heng, Anna Kilderry, Sarah Lambert, Bec Marland, Julianne Moss, Philippa Moylan, Mia Nosrat, Joanne O'Mara, Jo Raphael, Bethany Rice, Andrew Riordan, Amathullah Shakeeb, Roger Slee, Kitty te Riele, Matthew K. E. Thomas, Peter Walker, Scott Welsh, Ben Whitburn, Julie White and Michalinos Zembylas"--